2013
DOI: 10.1086/670325
|View full text |Cite
|
Sign up to set email alerts
|

Shell Technology, Rock Art, and the Role of Marine Resources during the Upper Paleolithic

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 23 publications
0
9
0
2
Order By: Relevance
“…A further corollary of the method presented here will be facilitation of a considerable improvement in the mapping and dating of the fluctuations evident in submerged prehistoric coastlines, because in the Stone Age, coasts represented the most attractive environments for exploitation and settlement by humans (Odum and Barrett, 2005). There has been increasing recognition of this by archaeologists in recent years, even though these coastal sites often lie submerged today and are therefore difficult to locate and study (Schackleton and van Andel, 1986;Parfitt et al, 2005;Richards et al, 2005;Jaksland, , 2009Bjerck, 2009;Wikell et al, 2009;Parfitt et al, 2010;Cortés-Sánchez et al, 2011;Ramos et al, 2011;Cuenca-Solana et al, 2013;Fischer et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A further corollary of the method presented here will be facilitation of a considerable improvement in the mapping and dating of the fluctuations evident in submerged prehistoric coastlines, because in the Stone Age, coasts represented the most attractive environments for exploitation and settlement by humans (Odum and Barrett, 2005). There has been increasing recognition of this by archaeologists in recent years, even though these coastal sites often lie submerged today and are therefore difficult to locate and study (Schackleton and van Andel, 1986;Parfitt et al, 2005;Richards et al, 2005;Jaksland, , 2009Bjerck, 2009;Wikell et al, 2009;Parfitt et al, 2010;Cortés-Sánchez et al, 2011;Ramos et al, 2011;Cuenca-Solana et al, 2013;Fischer et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Use-wear analysis showed that 57 limpets out of 602 specimens, primarily collected for consumption, were then used for scraping ochre utilized to paint the graphic representations in the cave [55]. Use of shell to obtain pigment is also documented at two other Upper Paleolithic Spanish cave sites (Fuente del Salin and Tito Bustillo in Cantabria) [56]. At Fuente del Salin two fragments of Patella were retouched to make them into borers [57].…”
Section: Shell Tools In Time and Spacementioning
confidence: 99%
“…Como hemos indicado en trabajos anteriores (Cuenca-Solana, 2014; Cuenca-Solana y Clemente-Conte, 2018), consideramos que esta situación muestra que probablemente el rol de estos instrumentos ha sido infravalorado dentro del abanico tecnológico empleado por los grupos humanos. El progresivo incremento durante los últimos años del análisis de este tipo de evidencias en contextos arqueológicos de Europa (ver, por ejemplo, Clemente-Conte et al, 2014; Courtin y Vigié, 1987;Cristiani et al, 2005;Cuenca-Solana, 2013;2015;Cuenca-Solana et al, 2010;2013a;2013b;2015;2016;Dupont y Cuenca-Solana, 2014;Gruet et al, 1999;Gutiérrez Zugasti et al, 2011;Pascual Benito, 2008;Maicas Ramos, 2008;Manca, 2013;2016;Rodríguez y Navarro, 1999;Tumung et al, 2012;2015;Vigié, 1987;1995;Vigié y Courtin, 1986), así como la variedad y calidad de los datos obtenidos, contribuye a reafirmar esta hipótesis. A continuación, mostraremos, a partir de la información etnográfica y de los resultados obtenidos en el análisis de diferentes contextos arqueológicos, las vinculaciones existentes entre el desarrollo de la actividad alfarera y el empleo de los instrumentos de concha.…”
Section: Instrumentos De Concha Para El Trabajo De Cerámicaunclassified